ALABAMA ARGILLACEA (HUBNER): LIFE CYCLE AND FOLIAR CONSUMPTION - ALVAREZ-R., J. ALONSO; SÁNCHEZ-C., GUILLERMO (Revista Colombiana de Entomología, 1982)
Although Alabama argillacea (Hübner) is a common cotton pest in Colombia, its life cycle and damaging capabilities have not been studied. In order to gather basic information about the mentioned topics a study was conducted in the Entomology Laboratory at the ICA Centro Regional de Investigaciones "Natalma" in El Espinal, Tolima. The Center has an altitude of 420 m.a.s.l. At 30 ± 2°C, the mean duration in days of the egg, larva, and pupa was 2,0; 10,72 and 6,9 respectively. Five instars were observed in the larval stage with durations of 2,0; 2,0; 1,0; 2,0 and 2,60 days each. During the first two instars, the larva eats up only on the leaf epidermis. During the last three instars, the mean leaf consumption per larva was: 2,25 cm2; 28,47 cm2; and 57,78 cm2; with a total average of 88.51 cm2.